Lifespan development of attentiveness in domestic dogs: drawing parallels with humans - Wallis, Lisa J.; Range, Friederike; Müller, Corsin A.; Serisier, Samuel; Huber, Ludwig; Virányi, Zsófia (Frontiers in Psychology, 2014)
Attention is pivotal to consciousness, perception, cognition, and working memory in all mammals, and therefore changes in attention over the lifespan are likely to influence development and aging of all of these functions. Due to their evolutionary and developmental history, the dog is being recognised as an important species for modelling human healthspan, aging and associated diseases. In this study, we investigated the normal lifespan development of attentiveness of pet dogs in naturalistic situations, and compared the resulting cross-sectional developmental trajectories with data from previous studies in humans. We tested a sample of 145 Border collies (six months to 14 years) with humans and objects or food as attention attractors, in order to assess their attentional capture, sustained and selective attention and sensorimotor abilities. Our results reveal differences in task relevance in sustained attentional performance when watching a human or a moving object, which may be explained by life-long learning processes involving such stimuli. During task-switching we found that dogs’ selective attention and sensorimotor abilities showed differences between age groups, with performance peaking at middle age. Dogs’ sensorimotor abilities showed a quadratic distribution with age and were correlated with selective attention performance. Our results support the hypothesis that the development and senescence of sensorimotor and attentional control may be fundamentally interrelated. Additionally, attentional capture, sustained attention and sensorimotor control developmental trajectories paralleled those found in humans. Given that the development of attention is similar across humans and dogs, we propose that the same regulatory mechanisms are likely to be present in both species. Finally, this cross-sectional study provides the first description of age group changes in attention over the lifespan of pet dogs.